Pengaruh Solvabilitas, Audit Tenure, Reputasi Kap Dan Umur Perusahaan Terhadap Ketepatan Waktu Penyampaian Laporan Keuangan - Amanda Farisa; Yunita Kurnia Shanti (CV. ITTC INDONESIA, 2025)
This study aims to analyze and prove the effect of solvency, audit tenure, KAP reputation and company age on the timeliness of financial report submission. This type of research is quantitative research. The population in this study are non cyclical consumer sector companies listed on the Indonesia Stock Exchange in the 2019-2023 period. The sampling technique used in this study uses the purposive sampling method. The population in the study was 129 companies and 65 companies met the sample criteria, after 41 outliers were taken. The analysis method used in this study is panel data regression analysis processed using the Eviews 12 application. The results of the study prove that partially: (1) Solvency does not affect the timeliness of financial report submission. (2) Audit tenure does not affect the timeliness of financial report submission. (3) KAP Reputation affect the timeliness of financial report submission. (4) Company Age does not affect the timeliness of financial report submission. While simultaneously Solvency, Audit tenure, KAP Reputation and Company Age affect the timeliness of financial report submission.